Kuasa Anak atas Perkawinan: Harmonisasi Perlindungan Anak dan Doktrin Fikih dalam Putusan Dispensasi Kawin - Muhammad Idris Nasution; Muhammad Syukri Albani Nasution (Yinyang: Jurnal Studi Islam Gender dan Anak, 2021)
Child marriage is a global phenomenon that often neglects the protection of children's rights, but a few parents use the jurisprudence doctrine as a shield against their actions. The fiqh doctrine that gives absolute power (ijbar) to fathers and grandfathers over their children's marriages is often abused to marry off children even without their consent. The voice of a child is considered insignificant and his rejection of the actions of his parents is often seen as a form of iniquity. It is different from the two decisions of the Religious Courts, which the authors found, in which the decisions were more concerned with the child's opinion on the marriage that was planned for him by giving the child the rights of isti'dzan and isti'mar. Regarding this case, the authors conducted an analysis with the perspective of child protection and maqashid sharia. The results of the analysis show that in the perspective of child protection and maqashid sharia, children should be rewarded for their opinions. But this award is not enforced absolutely because the opinions of parents cannot be ignored, especially in cases where there is a very urgent reason. So that it is necessary to harmonize the protection of children's rights with the fiqh doctrine of guardian authority by considering the best interests of the child.